O enfrentamento religioso em situação de migração - Santos, Neuza Botelho dos (2011)
The following essay aims the comprehension about the religious coping dealt upon migration. The phenomenological approach was chosen to reach its conclusions. From the current migratory reality, the possibility of religious coping was raised, considering the events of the migration process. The functions of religion were focused in the referred context. Up next, based on Pargament‟s studies upon the religious coping, it proceeds to the analysis of a report based on a migrant woman‟s experience. The results point the several religious practices that shall be proven effective on the field of religious coping in the referred situation. In that sense, it‟s verified the relation with sacred values, the insertion and communion in religious groups. Besides the solidarity and sharing of the same beliefs and values, possible resources become available for a migrant on the coping of issues found in his path, therefore providing help in finding a new meaning to his own experience